Removal of phosphorus and nitrogen in sediments of the eutrophic Stockholm archipelago, Baltic Sea - N. A. G. M. van Helmond; N. A. G. M. van Helmond; N. A. G. M. van Helmond; E. K. Robertson; E. K. Robertson; D. J. Conley; M. Hermans; C. Humborg; L. J. Kubeneck; L. J. Kubeneck; W. K. Lenstra; C. P. Slomp (Biogeosciences, 2020)
Coastal systems can act as filters for anthropogenic nutrient input into marine environments. Here, we assess the processes controlling the removal of phosphorus (P) and nitrogen (N) for four sites in the eutrophic Stockholm archipelago. Bottom water concentrations of oxygen (O2) and P are inversely correlated. This is attributed to the seasonal release of P from iron-oxide-bound (Fe-oxide-bound) P in surface sediments and from degrading organic matter. The abundant presence of sulfide in the pore water and its high upward flux towards the sediment surface (∼4 to 8 mmol m−2 d−1), linked to prior deposition of organic-rich sediments in a low-O2 setting (“legacy of hypoxia”), hinder the formation of a larger Fe-oxide-bound P pool in winter. This is most pronounced at sites where water column mixing is naturally relatively low and where low bottom water O2 concentrations prevail in summer. Burial rates of P are high at all sites (0.03–0.3 mol m−2 yr−1), a combined result of high sedimentation rates (0.5 to 3.5 cm yr−1) and high sedimentary P at depth (∼30 to 50 µmol g−1). Sedimentary P is dominated by Fe-bound P and organic P at the sediment surface and by organic P, authigenic Ca-P and detrital P at depth. Apart from one site in the inner archipelago, where a vivianite-type Fe(II)-P mineral is likely present at depth, there is little evidence for sink switching of organic or Fe-oxide-bound P to authigenic P minerals. Denitrification is the major benthic nitrate-reducing process at all sites (0.09 to 1.7 mmol m−2 d−1) with rates decreasing seaward from the inner to outer archipelago. Our results explain how sediments in this eutrophic coastal system can remove P through burial at a relatively high rate, regardless of whether the bottom waters are oxic or (frequently) hypoxic. Our results suggest that benthic N processes undergo annual cycles of removal and recycling in response to hypoxic conditions. Further nutrient load reductions are expected to contribute to the recovery of the eutrophic Stockholm archipelago from hypoxia. Based on the dominant pathways of P and N removal identified in this study, it is expected that the sediments will continue to remove part of the P and N loads.